AEU First Women's Conference, 1943 (pg. 5) (1943)
1943 1939-1945 "AEU First Women's Conference, 1943 (pg. 5)" [hfr0159e], 1943 The Amalgamated Engineering Union began to admit women as members in 1943, following the influx of women into the industry during the war, and rapidly began to specifically target women through booklets, separate conferences and a magazine. The AEU President, Jack Tanner, made this speech of welcome to the first Women's Conference.